The Role of Classroom Management in Shaping Students’ Character in Islamic Education at Elementary Islamic School - Auliyaur Rokhim (International Journal of Islamic Education Studies, 2026)
Classroom management is an important aspect of the learning process, particularly in Islamic Education, which is oriented not only toward academic achievement but also toward the formation of students’ character. However, in practice, various problems related to classroom management are still encountered, resulting in less optimal character development. This study aims to describe the role of classroom management in shaping students’ character in Islamic Education learning at MI Raudlatul Ulum Bojonegoro. This research employed a descriptive qualitative approach with research subjects consisting of Islamic Education teachers, the head of the madrasah, and students. Data were collected through observation, in-depth interviews, and documentation. Data analysis was conducted through data reduction, data presentation, and conclusion drawing, while data validity was ensured through source and technique triangulation. The results of the study indicate that classroom management implemented in a planned and consistent manner is able to create a conducive learning atmosphere and support the development of students’ discipline, responsibility, and politeness. Classroom management based on Islamic values and preventive in nature is in line with Jacob Kounin’s classroom management theory. The implications of this study show that strengthening teachers’ classroom management skills and support from the madrasah environment are essential so that Islamic Education learning is not only cognitively effective but also meaningful in shaping students’ character.